Endothelial cells regulate β-catenin activity in adrenocortical cells via secretion of basic fibroblast growth factor. (5th February 2017) - Schwafertz, Carolin; Schinner, Sven; Kühn, Markus C.; Haase, Matthias; Asmus, Amelie; Mülders-Opgenoorth, Birgit; Ansurudeen, Ishrath; Hornsby, Peter J.; Morawietz, Henning; Oetjen, Elke; Schott, Matthias; Willenberg, Holger S.
Abstract: Endothelial cell-derived products influence the synthesis of aldosterone and cortisol in human adrenocortical cells by modulating proteins such as steroidogenic acute-regulatory (StAR) protein, steroidogenic factor (SF)-1 and CITED2. However, the potential endothelial cell-derived factors that mediate this effect are still unknown. The current study was perfomed to look into the control of β -catenin activity by endothelial cell-derived factors and to identify a mechanism by which they affect β -catenin activity in adrenocortical NCIH295R cells. Using reporter gene assays and Western blotting, we found that endothelial cell-conditioned medium (ECCM) led to nuclear translocation of β -catenin and an increase in β -catenin-dependent transcription that could be blocked by U0126, an inhibitor of the mitogen-activated protein kinase pathway. Furthermore, we found that a receptor tyrosin kinase (RTK) was involved in ECCM-induced β -catenin-dependent transcription. Through selective inhibition of RTK using Su5402, it was shown that receptors responding to basic fibroblast growth factor (bFGF) mediate the action of ECCM. Adrenocortical cells treated with bFGF showed a significant greater level of bFGF mRNA. In addition, HUVECs secrete bFGF in a density-dependent manner. In conclusion, the data suggest that endothelial cells regulate β -catenin activity in adrenocortical cells also via secretion of basic fibroblast growth factor. Graphical abstract: Endothelial cell products are capable in regulating SF-1, StAR and CITED2, essential factor for adrenal organogenesis or function. However, the signaling involved was net yet conclusively described. Schwafertz et al. have found that β -catenin-mediated transcription is involved in the process and that endothelial cell products do not use the classical wnt-signaling pathway. The secretion of bFGF by endothelial cells partly explains the effects. Highlights: Endothelial cells induce β -catenin activity in adrenal cortical cells. Wnt-signaling, cAMP, Akt or PKC pathways are not involved. MEK, PI3-kinase and receptor tyrosine kinases are involved. Stimulation of β -catenin and StAR activity is partly mimicked by bFGF. bFGF is produced and secreted by human umbilical cord endothelial cells.